MOCCA: a 4k-pixel molecule camera for the position- and energy-resolving detection of neutral molecule fragments at CSR - Gamer, Lisa; Schulz, Dennis; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana; Kempf, Sebastian; Krantz, C.; Novotný, O.; Schwalm, D.; Wolf, A. (Journal of low temperature physics, 2016)
We present the design of MOCCA, a large-area particle detector that is developed for the position- and energy-resolving detection of neutral molecule fragments produced in electron-ion interactions at the Cryogenic Storage Ring at the Max Planck Institute for Nuclear Physics in Heidelberg. The detector is based on metallic magnetic calorimeters and consists of 4096 particle absorbers covering a total detection area of $$44.8\,mm × 44.8\,mm$$44.8mm×44.8mm. Groups of four absorbers are thermally coupled to a common paramagnetic temperature sensor where the strength of the thermal link is different for each absorber. This allows attributing a detector event within this group to the corresponding absorber by discriminating the signal rise times. A novel readout scheme further allows reading out all 1024 temperature sensors that are arranged in a $$32 × 32$$32×32square array using only $$16+16$$16+16current-sensing superconducting quantum interference devices. Numerical calculations taking into account a simplified detector model predict an energy resolution of $$Δ E_FWHM \le 80\,eV$$ΔEFWHM≤80eVfor all pixels of this detector.
Gesehen am 07.05.2020